Effect of surfactant dose on outcomes in preterm infants with respiratory distress syndrome: the OPTI-SURF study protocol - Goss,KCW; Gale,C; Malone,R; Longford,N; Ratcliffe,K; Modi,N (BMJ Open, 2020)
Introduction Respiratory distress syndrome is a condition seen in preterm infants primarily due to surfactant insufficiency. European guidelines recommend the dose and method of surfactant administration. However, in routine practice, clinicians often use a ‘whole vial’ approach to surfactant dosing. The aim of this study is to assess whether in preterm infants of gestational age 36+6 weeks+days or less, a low first dose of surfactant (100–130 mg/kg) compared with a high first dose (170–200 mg/kg) affects survival with no mechanical ventilation on either on postnatal days 3 and 4, and other outcomes.Methods and analysis In this prospective, observational study, we will use the National Neonatal Research Database as the main data source. We will obtain additional information describing the dose and method of surfactant administration through the neonatal EPR system. We will use propensity scores to form matched groups with low first dose and high first dose for comparison.Ethics and dissemination This study was approved by the West Midlands—Black Country Research Ethics Committee (REC reference: 18/WM/0132; IRAS project ID: 237111). The results of the research will be made publicly available through presentations at local, national or international conferences and will be submitted for publication in a peer-reviewed journal.Trial registration number NCT03808402; Pre-results.